Promoting sustainable evelopment by addressing the impacts of climate change response measures on developing countries - Martin Khor; Manuel F. Montes; Mariama Williams; Vicente Paolo B. Yu (South Centre, 2017)
Response measures arise in the context of developed and developing countries taking actions to combat climate change at global, national and regional levels, such as for the protection and stabilization of the climate, emissions leakages and/or the costs of environmental compliance. They may have unintended and adverse economic and social consequences for developing countries' economies, most often on the poorest and most vulnerable sectors of those economies.
Keywords: 300; Klimawandel; Nachhaltige Entwicklung; Entwicklungshilfe; Entwicklungsländer